Applications for using Risk Based Follow up Action Monitoring System - Suhardono, Sri (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Monitoring the follow-up action the management system is part of efforts to maintain performance, in an effort to achieve goals effective efficient and to be able to make continuous improvements. The agreed HSE (Health, Safety and Environment) work plan is used as a reference for making performance monitoring. The work plan matrix consists of 8 (eight) activities, divided into 30 (thirty) operational activities, and total of 155 (one hundred and fifty five) tasks. The follow-up closing performance of the data processed for 2022, was effectively covered by 86% with a total of 515 tasks, there were 1% (5 tasks) that had not been completed at the allotted time. Continuous improvement using risk control methods, with a focus on lowering low risk levels, there is an ALARP risk 12% (38 tasks), spread over environmental performance improvement 1%, HSE Communication 3%, emergency response readiness 2%, SMHSE 1% and contractor safety management system 1%. This tool can help organizations to monitor the follow-up action HSE plan from an effective, efficient side with high accuracy and determine continuous improvement with the ALARP method on each activity metric of the HSE work plan. The development for this tool is how effective, efficient and continuous improvement is divided into operational risk categories, corporate risk from where the risk is located as well as additional notifications for stakeholders in the organization